Kawin Tangkap di Sumba dan Ketidakadilan Gender - Konradus Doni Kelen (Ideas Publishing, 2022)
This research starts from concerns about the custom in Sumba which recognizes capture marriage as one of the choices of several ways to propose to a woman. The purpose of this research is to unravel the tangled threads of gender inequality in Sumba and to enlighten the Sumba people in general and women in particular about the importance of gender justice and the importance of respecting the human rights of a woman. The method used in this research is etnography with a qualitative descriptive approach. The results of this study show that the practice of capture marriage, which is a forced marriage practice, is actually very degrading to a womans dignity because marriage occurs without love but with the agreement of their parents. The data in this study will be obtained from field studies, observations and interviews and after that analyzed using reciprocity theory. The results of this study are hoped to be used as evaluation material for the Sumba people to immediately stop the practice of capture marriage. Penelitian ini bertolak dari keprihatinan akan adanya kebiasaan di Sumba yang mengenal kawin tangkap sebagai salah satu pilihan dari beberapa cara meminang seorang perempuan. Tujuan dari penelitian ini adalah ingin mengurai benang kusut ketidakadilan gender di Sumba dan ingin memberi pencerahan kepada masyarakat Sumba pada umumnya dan Perempuan pada khususnya akan pentingnya keadilan gender dan pentingnya menghargai hak-hak asasi seorang perempuan. Metode yang digunakan dalam penelitian ini adalah etnografi dengan pendekatan deskriptif kualitatif. Hasil penelitian ini menunjukkan praktek kawin tangkap yang adalah sebuah praktek kawin paksa sesungguhnya sangat merendahkan martabat seorang perempuan karena perkawinan terjadi tanpa cinta melainkan atas kesepakatan orang tua. Data dalam penelitian ini didapat dari studi lapangan, observasi dan wawancara dan setelah itu dianalisis dengan menggunakan resiprositas. Hasil penelitian ini diharapkan bisa menjadi bahan evaluasi bagi masyarakat Sumba supaya segera menghentikan praktek kawin tangkap.